PENGARUH PENYALURAN KREDIT TERHADAP PENDAPATAN BPR MURIA HARTA NUSANTARA - Dwi Rahmasari, Nadya; Muthmainnah, Muthmainnah (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2023)
This research was conducted with the aim of knowing how much influence lending has on bank income obtained by BPR Muria Harta Nusantara. The method used in this study is a quantitative method by utilizing secondary data originating from the annual published financial reports of BPR Muria Harta Nusantara for the 2018-2022 period. The hypothesis testing method uses simple linear analysis, t statistical testing (t test) and testing the coefficient of determination. The test results with simple linear analysis indicating that lending has a positive effect on bank income, with the t test results showing 6.542 > 3.182 and the results of the determination coefficient test showing R square of 0.934 which means lending affect the bank's income positively by 93.4% while the other 6.6% is influenced by other factors.